Credibility and Integrity of the Sukabumi City General Election Commission as the Organizer of the 2024 Election - Purwanti, Dian; Afriani, Dini Nuri; Fikri, Chaerul; Rahmawati, Selvi (Journal of Social and Policy Issues, 2024)
The purpose of this research is to determine the credibility and integrity of the Sukabumi City General Election Commission as the Organizer of the 2024 General Election. The grand theory in this research, the credibility variable theory uses source credibility proposed by Hovland, while the integrity variable theory uses the Executive Brand Assessment integrity concept in the Front Group Dissemination module Riau Provincial Government Integrity. The research method used is descriptive quantitative. The sampling technique that the researcher used was purposive sampling, with a population of 100 and a sample of 80 respondents and to collect data, the researcher carried out observations, literature studies and distributed questionnaires. Based on the correlation coefficient, it shows a very strong relationship between credibility, integrity and general elections, worth 0.826. Meanwhile, the coefficient of determination shows that the credibility and integrity of the General Election Commission (KPU) has a positive influence on the general election, namely 68.2%. Based on the results of this research, it shows that the Sukabumi City General Election Commission (KPU) has credibility and integrity as the organizer of the 2024 general election.